Mechanical ventilation with high tidal volume and associated mortality in the cardiac intensive care unit. (March 2014) - Shorofsky, Matthew; Jayaraman, Dev; Lellouche, Francois; Husa, Regina; Lipes, Jed
Abstract Background and objectives: Use of protective ventilation has been shown to decrease mortality in medical-surgical ICUs. There is limited data on tidal volume use in ventilated patients in the cardiac intensive care unit (CICU). We hypothesized that large tidal volumes are used in the CICU and that they could contribute to an increase in morbidity and mortality. Methods: We conducted a retrospective chart review of all mechanically ventilated patients with congestive heart failure or cardiac arrest in a single tertiary care CICU between April 2010 and February 2012. Ventilator settings were analyzed and tidal volume for predicted body weight (VT/PBW) was calculated for 51 patients. Results: The median initial tidal volume was 525 ml (IQR: 500–600) and median VT/PBW was 9.3 ml/kg (IQR: 8.3–10.1). Overall mortality was 29.4%. On univariate analysis, patients that received a VT/PBW below the median, mortality was 23.1% (95% CI: 7.9–39.3) compared to 36.0% (95% CI: 17.2–55.0) in patients that received a VT/PBW above themedian (P = 0.31). On multivariate analysis, the OR for death was 9.0 (95% CI: 1.3–62.0, P = 0.03) with VT/PBW above the median. Conclusion: Mechanical ventilation with high tidal volumes was associated with increased mortality in patients with congestive heart failure and post cardiac arrest in our CICU.